Multi-Objective Optimization of a T-Shaped Anti-Sloshing Baffle Based on NSGA-II - Lei, Yu; Zhang, Licheng; Zhong, Shengzhi; Huang, Bin (Frontiers in Energy Research, 2022)
Unlike the solid cargo in the truck, the liquid in the tank truck fluctuates with the movement of the vehicle. Most of the current research focuses on the transverse shock caused by the sloshing liquid and control of the liquid movement in the lateral direction. However, the movement of the fluid in the longitudinal direction also harms the vehicle dynamic. It is caused by the acceleration or deceleration of the truck. To lower the risk, the T-shape anti-sloshing baffle is designed based on the current research. To improve the conflict performance of the anti-sloshing baffle, the approximation model and multi-objective optimization method are initiated. The relationship between the anti-sloshing effect and the structure parameters of the anti-sloshing baffle is established by the Kriging method. The NSGA-II is initiated to minimize the maximum pressure caused by the moving liquid and the mass of the anti-sloshing baffle. The maximum pressure is decreased by 40.97% and the anti-sloshing baffle mass is decreased by 2.77%. With the optimized anti-sloshing baffle, the safety of the truck is improved.